Profesionalisme Guru Dalam Pembelajaran - Sofia Azhar (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
This journal discusses about the definition of teacher’s professionalism and the teaching, the terms of a professional teacher, the teacher’s performance, the ten qualities of the good teacher, the six of successful teacher’s characters, the unfortunate teacher’s character, the ten of teacher’s mistakes, the problem or difficulty of the teacher in learning